Progressive thought and the need to legitimize the inhuman. Observations on occasion of the centenary of the October Revolution (Colección, 2018)
The practiced Marxism, in its Leninist version (and many similar), has not actually represented the doctrine of the revolutionary proletariat, but the legitimating ideology of intellectual sectors which try to impose their own and unlimited political dominion. Until today this situation has not basically changed. It can be verified in the simplest ideological statement of this current: a socialist revolution justifies the use of every mean. Since Lenin, and including opponent tendencies within the Bolshevik movement, and also within the postmodernist relativism of Marxist congeniality, it has been impossible to develop a really critical Marxism without falling back in justifying ideologies.
Keywords: Ideology; Compensation mechanisms; Merleau-Ponty; Relativism; Socialism